Re-imaging Education Policy of a Framework Based on Indian Knowledge Systems - Nagendra Singh; Saurabh Pachauri; Manish Dixit (International Journal of Education Sciences, 2026)
Digital transformation revolutionized education; it enhances teaching and learning, improves administrative tasks, and empowers students and educators. Digital transformation in education and its importance in shaping the future. Integration of technology in classrooms enables interactive and immersive learning. Digital tools offer dynamic learning experiences, enhancing student engagement. This leads to improved comprehension and knowledge retention. Personalized learning experiences are facilitated by digital transformation. Digital transformation creates vast resources and online libraries, making knowledge accessible to all students regardless of location. Inaccessible information and resources are now easily accessed, enabling students to conduct research and broaden horizons. Knowledge has made education more inclusive, bridging the gap between students from diverse backgrounds. Digital transformation has optimized efficiency in educational institutions. Education 2.0 advocates a student-centered, technology-driven, experiential approach as a visionary framework for educational revolution. The main tenets, opportunities, and difficulties of Education 2.0 are examined in this abstract. Education 2.0 shifts focus to students, acknowledging current system flaws. Framework aims to foster love of learning, equip students with skills for changing environment. With personalized learning paths, students control their education speed. Technology enables global cooperation and interactive experiences. Experiential learning bridges theory with practical skills. Despite challenges, Education 2.0 faces implementation difficulties due to opposition, lack of resources, and need for teacher preparation. Collaborative efforts are required from educators, governments, parents, and communities to overcome these obstacles. It offers producing caring global citizens prepared for a changing world through innovation, adaptation, and empowering learners. Education 2.0 in the future calls for a collaborative commitment from students as active architects of their own knowledge and wisdom. The Research paper focuses on the role of Project-based learning and experiential learning approaches in the changing educational system worldwide. Both are influential strategies to provide practical learning from real experiences to students. Both approaches are increasingly used by teachers and students. This paper investigates collaborative works on different subjects along with technological intervention to identify existing knowledge and needs.
Keywords: Educational change; experiential learning; innovation and technology; project-based learning